Responsive neurostimulation with low‐frequency stimulation. Issue 2 (2nd December 2022) - Alcala‐Zermeno, Juan Luis; Starnes, Keith; Gregg, Nicholas M.; Worrell, Greg; Lundstrom, Brian N.
Abstract: Deep brain stimulation and responsive neurostimulation (RNS) use high‐frequency stimulation (HFS) per the pivotal trials and manufacturer‐recommended therapy protocols. However, not all patients respond to HFS. In this retrospective case series, 10 patients implanted with the RNS System were programmed with low‐frequency stimulation (LFS) to treat their seizures; nine of these patients were previously treated with HFS (100 Hz or greater). LFS was defined as frequency < 10 Hz. Burst duration was increased to at least 1000 ms. With HFS, patients had a median seizure reduction (MSR) of 13% (interquartile range [IQR] = −67 to 54) after a median of 19 months (IQR = 8–49). In contrast, LFS was associated with a 67% MSR (IQR = 13–95) when compared to HFS and 76% MSR (IQR = 43–91) when compared to baseline prior to implantation. Charge delivered per hour and pulses per day were not significantly different between HFS and LFS, although time stimulated per day was longer for LFS (228 min) than for HFS (7 min). There were no LFS‐specific adverse effects reported by any of the patients. LFS could represent an alternative, effective method for delivering stimulation in focal drug‐resistant epilepsy patients treated with the RNS System.